Pariwisata Kota: Pengkajian Dampak Mural Bermuatan Politik terhadap Wisatawan di Jalan Asia Afrika Bandung - Banon Gilang Muhamad Kali Ichsan; Andrea Abdul Rahman Azzqy; Citra Kemala Putri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Political murals along Jalan Asia Afrika in Bandung reveal a narrative void: there is no public art that explicitly commemorates the 1955 Asian-African Conference. This study examines three main aspects: (1) the existence of visual gaps found in cultural heritage areas. (2) How political murals influence perceptions, emotions, and intentions to revisit. (3) an integrated model for urban tourism that combines collaboration between policy makers, the arts community, an annual mural festival, and improvements in digital media. The qualitative-descriptive approach used involved comparative field studies in George Town (Penang), Lembur Katumbiri (Bandung), and Kali Code (Yogyakarta); two field observations with GIS mapping in four high-visibility corridors; in-depth interviews with the curator of the Asian-African Conference Museum and the mural community; focus groups with local artists; expert interviews on AR, projection mapping, and gamification; and an online perception survey (n = 150). Preliminary findings indicate the absence of KAA-themed murals, although community art interventions have increased visits by 35% and emotional connection by 78%. GIS outputs indicate four priority areas for an integrated mural program. Policy recommendations include formal partnerships between the KAA Museum, the Bandung City Government, and the art community; the implementation of an annual political mural festival; and the integration of AR/VR technology to promote educational impact.